Development of Problem-Based Math Learning Media using Adobe Animate to Improve Fourth-Grade Students’ Learning Outcomes on Fraction - Khasanah, Lathifatul; Ansori, Isa (FKIP Universitas Lampung, 2025)
This study aims to develop interactive learning media based on Adobe Animate with the Problem-Based Learning (PBL) model to improve student learning outcomes on fraction material in class IV SDN Kedungpane 02. The background of this research is based on students' low understanding of the concept of fractions, which is caused by the lack of use of innovative learning media and less interesting learning methods. Therefore, Interactive Math media was developed that integrates animation and interactivity in the learning process to increase student engagement and understanding. This research uses the Research and Development (R&D) method with the ADDIE development model which consists of five stages, namely Analysis to identify learning needs, Design to design appropriate media Development to build products, Implementation to test on students, and Evaluation to assess the effectiveness of the media that has been developed. Data were collected through observation, interviews, questionnaires, documentation, and learning outcomes tests. The validity test was carried out by media experts and material experts, while the media effectiveness test was carried out through experiments with a pretest-posttest control group design. The results showed that the Interactive Math media based on Adobe Animate is very valid and feasible to use in learning based on expert validation with a score of 91.07% from material experts and 91.66% from media experts. In addition, there was a significant increase in student learning outcomes after using this media, as evidenced by the difference in the average scores of the pretest and posttest in the small and large groups. Thus, Adobe Animate-based interactive learning media with PBL model can be an innovative solution in improving students' understanding and learning outcomes on fraction materials. This study recommends the use of similar media on other materials to improve the effectiveness of learning in elementary schools. Keywords: adobe animate, interactive learning media,fraction, problem based learning (PBL), learning outcomes.